C2 HEST Score and Prediction of Incident Atrial Fibrillation in Poststroke Patients: A French Nationwide Study. Issue 13 (2nd July 2019) - Li, Yan‐Guang; Bisson, Arnaud; Bodin, Alexandre; Herbert, Julien; Grammatico‐Guillon, Leslie; Joung, Boyoung; Wang, Yu‐Tang; Lip, Gregory Y. H.; Fauchier, Laurent
Abstract : Background: The C2 HEST score (coronary artery disease or chronic obstructive pulmonary disease [1 point each]; hypertension [1 point]; elderly [age ≥75 years, 2 points]; systolic heart failure [2 points]; thyroid disease [hyperthyroidism, 1 point]) was initially proposed for predicting incident atrial fibrillation (AF) in the general population. Its performance in poststroke patients remains to be established, especially because patients at high risk for incident AF should be targeted for more comprehensive screening. This study aimed to evaluate this newly established incident AF prediction risk score in a post–ischemic stroke population. Methods and Results: Validation was based on a hospital‐based nationwide cohort with 240 459 French post–ischemic stroke patients. Kaplan–Meier curves for incident rate of AF depict differences between varying risk categories. Discrimination of the C2 HEST score was evaluated using the C index, the net reclassification index, integrated discriminatory improvement, and decision curve analysis. During 7.9±11.5 months of follow‐up, 14 095 patients developed incident AF. The incidence of AF increased from 23.5 per 1000 patient‐years in patients with a C2 HEST score of 0 to 196.8 per 1000 patient‐years in patients with a C2 HEST score ≥6. Kaplan–Meier curves showed a clear difference among different risk strata (log‐rank P <0.0001). The C2 HEST score had good discrimination with a C index of 0.734 (95% CI, 0.732–0.736), which was better than the Framingham risk score and the CHA2 DS2 ‐VASc score (congestive heart failure, hypertension, age ≥75 [doubled], diabetes mellitus, stroke [doubled], vascular disease, age 65 to 74 years, and female sex) ( P <0.0001, respectively). The C2 HEST score was also superior to the Framingham risk score and the CHA2 DS2 ‐VASc score as shown by the net reclassification index, integrated discriminatory improvement ( P <0.0001, respectively) and decision curve analysis. Conclusions: The C2 HEST score performed well in discriminating the individual risk of developing incident AF in a white European population hospitalized with previous ischemic stroke. This simple score may potentially be used as a risk stratification tool for decision making in relation to a screening strategy for AF in post–ischemic stroke patients.